PENGARUH KOMPETENSI DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL TANGERANG SELATAN - Yandina, Febrin; N Lilis Suryani (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to determine the effect of Competence (X1) and Communication (X2) on Employee Performance (Y) at the Department of Population and Civil Registration of South Tangerang City. The research method used is descriptive quantitative with an associative approach. The population in this study consisted of 200 employees, with a total sample of 67 respondents determined through the distribution of questionnaires. The results of the partial test (t-test) show that the Competence variable (X1) has a positive and significant effect on Employee Performance, with a t-value of 3.119 > t-table 1.997 and a significance value of 0.003 < 0.05. The Communication variable (X2) also has a positive and significant effect on Employee Performance, with a t-value of 7.836 > t-table 1.997 and a significance value of 0.000 < 0.05. The simultaneous test (F-test) results indicate that Competence and Communication together have a positive and significant effect on Employee Performance, with an F-value of 35.134 > F-table 3.140 and a significance value of 0.000 < 0.05. The simultaneous correlation coefficient (R) of 0.723 shows a strong relationship between Competence and Communication with Employee Performance, while the coefficient of determination (Adjusted R²) of 0.508 indicates that 50.8% of the variation in Employee Performance can be explained by Competence and Communication, while the remaining 49.2% is influenced by other factors outside this study.